Towards Sustainable and Ethical Food Systems: Exploring Consumer Motivations and Strategies for Plant-Based Eating - Perussello, Camila Augusto; Caprioglio Panizza, Silvia; Herrero-Langreo, Ana (Wiley, 2025)
Transforming global food systems is crucial for mitigating environmental degradation, reducing the global disease burden andprotecting sentient individuals from harm. Despite overwhelming evidence linking animal-sourced foods to ecological dam-age, resource depletion and public health challenges, gaps remain in promoting sustainable consumption. This urgency is com-pounded by the scientific recognition of animal sentience, which elevates animal use to a moral issue. This study combinesempirical data from a survey of 500 respondents with a literature review to explore motivations and behaviours driving plant-based eating. Key suggested interventions to foster a responsible food system include: (i) raising awareness of animal rights, (ii)disseminating nutritional and environmental knowledge, (iii) reforming agri-food subsidies, (iv) promoting plant-based foodresearch, commercialisation and consumption and (v) fostering social inclusion and positive recognition of vegan identity. Byaddressing psychological, social and structural barriers to animal-free diets, this study offers actionable strategies for advancinga sustainable future.
Keywords: animal rights; environmental sustainability; ethical consumption; plant-based diets; public health; social justice; sustainable food systems